PENATALAKSANAAN KISTA RADIKULERPADA MAKSILA ANTERIOR SECARA ENUKLEASI - H. Mawardi; M. Hendra Chandha (Journal of Dentomaxillofacial Science, 2002)
A radiculer cyst is an odontogenic cyst which most frequentlyencounterd. Usually these cysts grew up around the tip oftooth root. They had arisen resulting from an inflammatoryprocess and generally started by a presence of granuloma. Awell of radiculer cyst consisted of stratified squamousepithelium. In the initial stadium, these cyst do not give thesymptoms. They are often discovered incidentally in theradiographic examination ofnon vital tooth root. Nevertheless,these cyst can grow to become greater progressivelly, so thatleading to facial deformity. If bone layers have flattened,would be encountered a ping pong ball phenomenon andthere have been a fluctuation and the treatment was done byenukleation technique.